2016
DOI: 10.7556/jaoa.2016.091
|View full text |Cite|
|
Sign up to set email alerts
|

Assessment of Research Interests of First-Year Osteopathic Medical Students

Abstract: First-year osteopathic students may have comparable amounts of research experience as allopathic medical students. Although these findings are limited to 2 campuses of 1 osteopathic medical school, they suggest that first-year osteopathic medical students are highly motivated to participate in research while in medical school.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 1 publication
1
7
0
Order By: Relevance
“…One exception to note regarding the U.S. medical education landscape, however, is that exposure of osteopathic (DO) medical students to research is still in an early growth phase with limited data compared to their allopathic (MD) counterparts [20] hence its relative over representation in the U.S. literature in this current study. According to the National Resident Matching Program match data, U.S. allopathic students lead in the number of research experiences, followed by non-U.S. international medical graduates (IMG), U.S. IMG’s, and then osteopathic medical students [21–23].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One exception to note regarding the U.S. medical education landscape, however, is that exposure of osteopathic (DO) medical students to research is still in an early growth phase with limited data compared to their allopathic (MD) counterparts [20] hence its relative over representation in the U.S. literature in this current study. According to the National Resident Matching Program match data, U.S. allopathic students lead in the number of research experiences, followed by non-U.S. international medical graduates (IMG), U.S. IMG’s, and then osteopathic medical students [21–23].…”
Section: Discussionmentioning
confidence: 99%
“…One common strand that was found in the perspectives of research during medical education was the medical students’ expressed interest and positive attitude toward research [20,27,28]. Overall, medical students viewed research as useful and important to their education [29,30].…”
Section: Discussionmentioning
confidence: 99%
“…Although a large number of students enrolled in osteopathic medical school have a research background, it has been hypothesized that a lack of research training during medical school may play a key role in the decreased publication rate of osteopathic physicians [9-10]. The Fresno test was designed to evaluate a learner’s knowledge in evidence-based medicine and has been externally validated [11].…”
Section: Discussionmentioning
confidence: 99%
“…In our experience, interviews provide an opportunity to probe further into students’ interests and to determine compatibility with potential mentors and projects. Nearly all SRPs offered clinical research options, which 3 prior survey studies have shown to be the most popular type of research for OMSs (65.5–82.0%) [ 16 , 20 , 21 ]. A majority of SRPs provided research lectures or didactics.…”
Section: Discussionmentioning
confidence: 99%